Lawyers Should Be Lawyers, But What Does That Mean?: A Response to Aiken & Wizner and Smith - Katherine R. Kruse (Washington University Journal of Law & Policy, 2004)
Lawyers should be more like social workers. That is the message of Law as Social Work, the provocative essay by Jane Aiken and Stephen Wizner (Aiken & Wizner) in the Washington University Journal of Law & Policy volume, which preceded the conference on Promoting Justice Through Interdisciplinary Teaching, Practice, and Scholarship, hosted by Washington University School of Law in March 2003. This Essay begins with a review of the Aiken & Wizner and Smith Articles, pointing out the themes that are common to both and the tensions in their competing visions of justice and professionalism. The second part of the Essay explores the tensions between the professional perspectives of lawyers and social workers, as reflected in their differing conceptions of social justice, and analyzes how those differing visions affect issues of systemic role and relationships with clients. The third part turns to a discussion of how these tensions have played out in the field of juvenile justice, in which law and social work have historically interacted. The Essay concludes by affirming the traditional adversarial ethical role of lawyers, while further suggesting ways in which the work of lawyers can be broadened and enhanced by embracing some aspects of the social work perspective.
Keywords: Multidisciplinary practices; Legal ethics; Social workers; Juvenile justice administration